Inca gold - Cussler, Clive (Cussler, Clive. Dirk Pitt adventure., 2007)
Saving the lives of two American archaeologists who nearly drown in a sacrificial pool in the Andes Mountains, Dirk Pitt becomes unwittingly involved in a sinister crime organization that has discovered an ancient treasure.